Zenbaki-lerroa: osoak / diseinu nagusia, Amanda McGarry; software-garapena, John Blanco, Chris Klusendorf, Saurabh Totey; [itzulpena, José Manuel López Irastortza] - McGarry, Amanda; Blanco, John; Klusendorf, Chris; Totey, Saurabh; López Irastorza, José Manuel
Zenbaki-lerroa ulertzeko simulazio interaktiboa.